On the optical nonlinearity in the GeSbSe chalcogenide glasses. (10th June 2020) - Nedelcu, Nicoleta; Chiroiu, Veturia; Munteanu, Ligia; Girip, Iulian
Abstract: Chalcogenide glasses Gex Sb40−x Se60 with composition 12, 25 and 30 at.%, synthesized from elements with 5N purity (Ge, Sb, Se) by the conventional melt-quenching method were studied. The spectrophotometer's measurements were recorded to determine the optical properties. Models based on the absorbance and absorption coefficient are used to determine the optical band-gap energy. The Urbach energy is deduced in the Ge x Sb 40 − x Se 60 thin film alloys with composition x  = 12, 25 and 30 at.%. The electronic and structural properties are studied, and the influence of the Urbach energy in estimating of the nonlinearity in the optical properties of these glasses is discussed. The analysis is performed with respect to the Urbach parameter that quantifies the degree of crystallinity of the structure which can be used to understand the behavior of different diffractive, wave-transmission and fiber structures.